Lactic Acid Production from Distiller’s Dried Grains Dilute Acid Hydrolysates - Greta Naydenova; Petya Popova-Krumova; Svetla Danova; Dragomir Yankov (Fermentation)
Lactic acid (LA) is an important chemical with diverse applications in various industries. LA can be produced by the fermentation of different substrates by many microorganisms such as bacteria, fungi, yeasts, and algae. Lactic acid bacteria (LAB) are generally accepted as the main producers of LA. A distinct characteristic of LAB is the complexity of the fermentation media. Distiller’s dried grains with solubles (DDGS), a by-product from bioethanol production, represent a promising substitute for costly sugars in the nutrition media for LA production. In the present paper, the possibility of using dilute acid DDGS hydrolysates as a substrate for LA fermentation was investigated. The influence of different factors (acid concentration, time, pressure, solid-to-liquid ratio) on the reducing sugars (RS) obtained was studied. Additional enzyme hydrolysis was carried out to increase RS content in the hydrolysates. LA production from hydrolysates without and with control of the pH during fermentation was monitored and compared with lactose as a substrate. Inhibition of the process was observed in both substrates in the absence of pH control which was overcome in the case of pH control. A mathematical model based on the Verhulst and Ludeking–Piret equations was proposed and tested, showing very good agreement with experimental data.